Gene Mutations Related to Glucocorticoid Resistance in Pediatric Acute Lymphoblastic Leukemia - Zhang, JinFang; Zeng, LingJi; Wang, YuLian; Pan, JianWei; Li, XingDong; Feng, Bei; Yang, Quan (Frontiers in Pediatrics, 2022)
Objective: To investigate the correlation between gene mutations and glucocorticoid resistance in pediatric acute lymphoblastic leukemia (ALL). Methods: A total of 71 children with ALL admitted to our center between September 2019 and September 2021 were enrolled. DNA obtained from bone marrow or peripheral blood samples at initial diagnosis was used for genetic testing via whole exome sequencing. Meanwhile, patient clinical information was collected. Subsequently, the correlations of gene mutations with clinical features and glucocorticoid resistance were analyzed. Results: Of the 71 children enrolled, 61 (85.9%) had B-cell ALL (B-ALL) and 10 (14.1%) had T-cell ALL (T-ALL). The five genes with the highest mutation frequency in B-ALL were TTN (24.4%), FLT3 (14.6%), TP53 (14.6%), MUC16 (9.8%), and EPPK1 (9.8%). In contrast, those with the highest frequency in T-ALL were NOTCH1 (54.5%), FBXW7 (27.3%), TTN (27.3%), MUC16 (27.3%), and PHF6 (18.2%). Upon statistical analysis, TTN and NOTCH1 mutations were found to be associated with prednisone resistance. Further, TTN and MUC16 mutations were associated with a lower age at diagnosis, and NOTCH1 mutations were associated with T-ALL in female patients. Leukocyte counts and LDH levels did not differ based on the presence of any common gene mutation, and no association between these gene mutations and overall survival was observed. Conclusions: Our study is the first to demonstrate the association between TTN mutation and glucocorticoid resistance in ALL. Our findings could guide strategies for overcoming drug resistance and aid in the development of drug targets.